The roles of some antecedents of broadband user behavioural intention among students in the rural areas through PLS-SEM - Muraina, Ishola D.; Sheik Osman, Wan Rozaini; Ahmad, Azizah (Science Publications, 2015)
The insufficient broadband enabled-services in the rural areas have been identified among the reasons that prolong the behaviour of rural dwellers on the use of low-band internet while government agencies have started initiations to increase the use of broadband in the rural area.However, previous studies have failed to identify the roles played by antecedents of broadband user behavioural intention in the rural communities. Thus, this research investigates roles of some antecedents of broadband user behavioural intention in the rural areas by adapting UTAUT model.A quantitative research approach was employed by engaging 1,730 participants from 40 villages who are secondary school students that are living in rural areas of northern region of Malaysia.The result reveals that performance expectancy, effort expectancy and compatibility have large effect on broadband user behavioural intention in the rural areas, while social influence recorded medium effect.This implies that all the identified factors may help in determining the behavioural intention of users of broadband in the rural areas.